If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6m = 2(3n + -1) Reorder the terms: -6m = 2(-1 + 3n) -6m = (-1 * 2 + 3n * 2) -6m = (-2 + 6n) Solving -6m = -2 + 6n Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Divide each side by '-6'. m = 0.3333333333 + -1n Simplifying m = 0.3333333333 + -1n
| 81-(8*9)= | | 4n+24n-12=-12-32n | | 27x-4=136 | | -8=-3(3)+b | | (2/x-7)-(4/3x-6) | | 2*x-2=4 | | 20p-2y=14 | | 5x^2+32+1=-7x+9 | | 81-8*9= | | .4(3.2+2)-x=2x+1.8 | | 6xsquared-3x+1forx=-2 | | 3z+5=1 | | x+(x-7)+3(x-7)=107 | | 10x-20=8x+16 | | 38-3x=-1-30x-42 | | 4x^2+11x-2=9x | | 2.5-11=28 | | 7x4y9/3 | | 2sin^2x=2sin+4 | | x=90+-1.5y | | 6x-x-8=2 | | Lny=-0.28 | | 7x=5y+30 | | 15=12+v | | -20-2n=24n+6 | | 2.5(6x+4)-5=12x+35 | | 3/x-7=21 | | y=17(x^2-9x+1) | | .089-7.18x=x | | 6b+34=8b | | 10+2x=16-4x | | 7x-2/6=1 |